Changing the organizational culture to transform the economy: The case of Greece - Boufounou, Paraskevi; Argyrou, Maria Despoina (Frontiers in Research Metrics and Analytics, 2022)
Introduction Organizational culture determines the ability of companies to adapt, transform, and innovate, thereby directly affecting their profitability and competitiveness. However, the same applies to the public sector since, now more than ever, it has to be agile in order to shield its society and economy against modern challenges (such as COVID-19, climate change, and digitalization). This article uses the case of Greece as an example to present the need for change in organizational culture to unlock its development and growth potential through transformation, adaptation, and innovation. To support our argument, we combine the findings of the international literature regarding the relationship between organizational culture and the aforementioned elements, as well as empirical evidence from Greece. Methods In particular, we assess organizational culture pertaining to the major sector reforms that took place in Greece, as a result of the recent economic and financial crisis, by presenting and evaluating comparative empirical findings on the characteristics of the prevailing and desired future organizational culture. Results and discussion Examining and comparing the results of previous studies in Greece that used the Organizational Culture Assessment Instrument (OCAI) questionnaire survey in both private (such as banking and telecoms) and public sectors (such as social security, public revenues authority, and hospitals), two interesting results arise: (i) there is a clear distinction between the public sector and the private sector, with the former being mainly characterized by “hierarchy culture,” while the latter by “market culture” and (ii) in both sectors and all industries/services, the desire to prevail in future organizational culture is the “clan culture.” These findings are of immense importance as organizational culture issues play a key role in formulating future strategic plans, enabling the development of key sectors of the Greek economy and enhancing effective governance and social services. Concisely, our results draw useful conclusions for policy implications and academics, implying that there is an emergent need for organizational transformation in both private and public sectors in Greece, which can be achieved through new innovative methods of organization and operation, creating a new more agile, adaptive, and innovative culture.